Environmental justice as social consciousness in times of negationism (Research, Society and Development, 2022)
This critical-reflective essay seeks to discuss the role of environmental justice as a social conscience, articulating the discussion with the need to think about the challenges in times of denialism. A question that arises here is: how can social conscience interfere in the construction of environmental justice, from a local social context, with global influence in times of denialism? The main objective of this text concerns to face the contemporary debate around the concepts of environmental justice and social conscience, in order to intervene in a qualified way so that the current situation is modified. The research was developed using the dialectical method, through the qualitative approach, with documental research techniques - bringing legal and bibliographic aspects. Among the results that can be pointed out are the identification of established human relationships that, at times, have caused damage to environmental issues arising from a challenging context and the modus operandi as a form of critical resistance that opposes this denialism.